From cellular doses to average lung dose. Issue 1 (27th April 2015) - Hofmann, W.; Winkler-Heil, R.
Abstract : Sensitive basal and secretory cells receive a wide range of doses in human bronchial and bronchiolar airways. Variations of cellular doses arise from the location of target cells in the bronchial epithelium of a given airway and the asymmetry and variability of airway dimensions of the lung among airways in a given airway generation and among bronchial and bronchiolar airway generations. To derive a single value for the average lung dose which can be related to epidemiologically observed lung cancer risk, appropriate weighting scenarios have to be applied. Potential biological weighting parameters are the relative frequency of target cells, the number of progenitor cells, the contribution of dose enhancement at airway bifurcations, the promotional effect of cigarette smoking and, finally, the application of appropriate regional apportionment factors. Depending on the choice of weighting parameters, detriment-weighted average lung doses can vary by a factor of up to 4 for given radon progeny exposure conditions.